Hydrothermally grown ZnO nanorods on cellulose filter papers for piezo-photocatalysis applications - Songpanit, Maneerat; Limwichean, Saksorn; Horprathum, Mati; Boonyarattanakalin, Kanokthip; Pecharapa, Wisanu; Mekprasart, Wanichaya (My University, 2025)
ZnO nanorods were grown on cellulose filter paper using a one-pot hydrothermal method, varying concentrations at 10, 50, and 100 mM. The growth of ZnO nanorods exhibited high crystallinity in ZnO wurtzite confirmed by XRD and SEM results. Meanwhile, the specific surface area of all samples decreased following higher seed concentrations. To evaluate the photocatalytic performance, all samples were tested using RhB degradation under xenon irradiation, ultrasonic treatment, and a combination of xenon and ultrasonic irradiation. The highest ZnO catalytic performance in photocatalytic and piezo-catalytic reactions was observed at a 50 mM seed layer concentration attributing to the strong crystallinity along the c-axis direction and high aspect ratio of nanorods. Moreover, the optimal condition for piezo-photocatalytic applications was achieved by the seed layer concentration at 10 mM, resulting in shorter nanorods and a large surface area, providing better mechanical stability under stress corresponding to enhancing the charge recombination in photocatalytic processes.
Keywords: Hydrothermal; Piezo-photocatalysis; ZnO